THE EFFECT OF HARVEST PRODUCTIVITY AND RICE HARVEST PRICES ON THE WELFARE LEVEL OF FOOD CROP FARMERS IN EAST JAVA 2014-2024 - Sarirotul 'Alim; Rokhmat Subagiyo; Ummu Sholihah (JURNAL PROFIT, 2025)
Agriculture is a strategic sector for Indonesia's economy, and East Java is a major contributor to national rice production due to its large harvested area and high productivity. However, farmer’s welfare remains relatively stagnant, reflected in the Farmer's Term of Trade Indeks (NTP) which has only ranged between 100-105 during 2014-2025. This study aims to analyze the effect of harvest productivity and rice harvest prices on the welfare level of food crop farmers in East Java. This research using a quantitative approach and data analysis was carried out using multiple linear regression with harvest productivity, rice harvest prices, and the NTP as indicators of farmer’s welfare. The data used is secondary time series data for the period 2014-2024 from the East Java Central Bureau of Statistics (BPS). The results indicate that both rice harvest productivity and rice harvest price have a positive but not signifficant effect on farmer’s welfae. The coefficient of determination (Adjusted R²) of 0.260 shows that only 26% of variations in farmers' welfare can be explained by these two variables, while 74% are influenced by other factors. These findings suggest that increases in yield and market prices have not yet been able to significantly improve farmers' welfare and are contrary to the Islamic economic perspective, which emphasizes fair distribution of value and benefits. This study recommends the need for agricultural policy interventions that are fair, sustainable, and in line with Islamic economic principles.